Indonesia's Economic Potential in The South Pacific and The Urgency of Joining The South Pacific Defense Ministers Meeting Forum - Kristin Megalin Walukow Seso; Panji Suwarno; Sri Sundari (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2025)
The South Pacific is a region that is a new arena for the struggle for hegemony by big countries in the world. This area is very strategic, both for the economic and defense sectors. Apart from France and Australia, which have long had a strong influence in the region, the United States, China, Japan and the UK have also begun to explore the South Pacific. Even though the South Pacific is not as popular as the Southeast Asia region, Indonesia actually has interests in the region. Its geographic location is close to the South Pacific, and its similarities as an archipelagic country as well as its large economic potential and security threats encourage Indonesia to be actively involved in the region. For this reason, the Indonesian Government, through the Ministry of Defense, expressed its desire and hope that Indonesia would participate in the South Pacific Defense Ministers Meeting (SPDMM) forum.